Popper and Hayek on the principle of unintended consequences - Hacıhamdioğlu, Cavit. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The use of the principle of unintended consequences has an important place to legitimize or deligitimize the role of state intervention in the market. The conservative liberal, like Hayek, uses the principle of unintended consequences to indicate the dangers of state intervention due to its damaging effect on society and market. Hayek, at the background, implicitly stresses the beneficial aspects of unintended consequences, since he believes that problems will be solved favorable to all in the self-regulating market. Contrary to Hayek, Popper used the principle to indicate dangers of both market and state actions but asked for democratic state intervention. He suggested the unintended harmsgive state a legitimate moral reason to intervene in the market and solve social problems. Importance of the principle is that it can be used to maintain the status quo or to solve social problems. Hayek̕s usage of the principle serves the first and should be rethought in an age when many social problems, such as poverty and unemployment are seen to beinsoluble without doing harm to the market. The potential risks involved due to negative unintended consequences of human actions should not prevent the solution of avoidable problems by state. If the principle is used in an ideological way, it produces excuse, leads to irresponsibility, and allows problems toaggregate. A scientific approach, however, try to solve social problems without finding ideological excuses. Therefore, a scientific approach to unintended consequences and rational-scientific use of the principle of unintended consequences can be a good starting point for social problem solving in which state intervention becomes necessary.